2017
DOI: 10.1016/j.jns.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of cognitive impairment in individuals with essential tremor

Abstract: Objective The extent to which individuals with ET who have clinically significant cognitive impairment are aware of their cognitive changes is unclear. Reduced awareness has important implications for everyday function and decision-making. Methods 150 individuals with ET (109 Normal Cognition (ET-NC group), and 30 with MCI and 11 dementia (ET-CI group)) completed self-ratings and objective assessments of memory, language, and executive functioning. Discrepancy scores were calculated to assess awareness of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The CCI-20’s ability to identify subtle executive deficits may relate to the fact that the executive domain was objectively the lowest (i.e., lowest z-score composite), corresponding to observations that weaknesses/impairment in executive function tasks are among the most common cognitive sequelae in PD and ET cohorts. While studies on SCCs in ET are extremely limited, our findings align with those of Azar and colleagues (2017), who demonstrated that cognitively unimpaired ET individuals accurately perceive their executive function abilities. Prior studies in PD, however, have failed to identify a direct relationship between subjective and objective measures of executive function (Koerts et al, 2011, 2012; Lanni et al, 2014; Vlagsma et al, 2017), consistent with our results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The CCI-20’s ability to identify subtle executive deficits may relate to the fact that the executive domain was objectively the lowest (i.e., lowest z-score composite), corresponding to observations that weaknesses/impairment in executive function tasks are among the most common cognitive sequelae in PD and ET cohorts. While studies on SCCs in ET are extremely limited, our findings align with those of Azar and colleagues (2017), who demonstrated that cognitively unimpaired ET individuals accurately perceive their executive function abilities. Prior studies in PD, however, have failed to identify a direct relationship between subjective and objective measures of executive function (Koerts et al, 2011, 2012; Lanni et al, 2014; Vlagsma et al, 2017), consistent with our results.…”
Section: Discussionsupporting
confidence: 90%
“…As such, cognitive complaints in this setting may not reflect their prevalence in a large community-based population. Finally, the current study did not examine differences in SCCs between cognitively intact and impaired individuals, despite evidence to suggest awareness decreases with cognitive impairment and transition to MCI (Azar et al, 2017;Copeland et al, 2016;Pennington et al, 2021).…”
Section: Discussionmentioning
confidence: 88%
“…Although early descriptions of essential tremor did not identify cognitive impairments, pre-surgical neuropsychological assessments identified impairments, sparking further studies. The impairment is typically mild and is often not recognized by the patient 6667. A 2012 literature review of cognition in essential tremor reported that mild executive dysfunction was a consistent finding in studies.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Moreover, given that AD and FTD, and other neurodegenerative diseases, include other cognitive deficits (e.g., executive function and language), such domains are increasingly becoming the focus of metacognitive research in dementia and its precursor, Mild Cognitive Impairment (MCI) [3, 21]. In the past decade, there has also been increasing examination of the integrity of self-awareness in populations not typically characterized by profound disturbances in awareness such as Parkinson's disease [22, 23] and Essential Tremor [15], with evidence suggesting that elements of self-awareness may deteriorate in these conditions as well.…”
Section: Self-awareness Across Neurodegenerative Diseasesmentioning
confidence: 99%